Inferior Vena Cava Filter in a Patient with COVID-19 Pneumonia to Prevent a Massive Pulmonary Embolism - Cena, Tiziana (Ann Vasc Surg, 2020)
COVID 19 predispose to deep vein thrombosis. We describe an early placement of inferior vena cava filter added to the therapeutic anticoagulation to prevent a massive pulmonary embolism.